Neogene paleogeography provides context for understanding the origin and spatial distribution of cryptic diversity in a widespread Balkan freshwater amphipod - Grabowski, Michał (PeerJ, 2017)
BACKGROUND: The Balkans are a major worldwide biodiversity and endemism hotspot. Among the freshwater biota, amphipods are known for their high cryptic diversity. However, little is known about the temporal and paleogeographic aspects of their evolutionary history. We used paleogeography as a framework for understanding the onset of diversification in Gammarus roeselii: (1) we hypothesised that, given the high number of isolated waterbodies in the Balkans, the species is characterised by high level of cryptic diversity, even on a local scale; (2) the long geological history of the region might promote pre-Pleistocene divergence between lineages; (3) given that G. roeselii thrives both in lakes and rivers, its evolutionary history could be linked to the Balkan Neogene paleolake system; (4) we inspected whether the Pleistocene decline of hydrological networks could have any impact on the diversification of G. roeselii. MATERIAL AND METHODS: DNA was extracted from 177 individuals collected from 26 sites all over Balkans. All individuals were amplified for ca. 650 bp long fragment of the mtDNA cytochrome oxidase subunit I (COI). After defining molecular operational taxonomic units (MOTU) based on COI, 50 individuals were amplified for ca. 900 bp long fragment of the nuclear 28S rDNA. Molecular diversity, divergence, differentiation and historical demography based on COI sequences were estimated for each MOTU. The relative frequency, geographic distribution and molecular divergence between COI haplotypes were presented as a median-joining network. COI was used also to reconstruct time-calibrated phylogeny with Bayesian inference. Probabilities of ancestors’ occurrence in riverine or lacustrine habitats, as well their possible geographic locations, were estimated with the Bayesian method. A Neighbour Joining tree was constructed to illustrate the phylogenetic relationships between 28S rDNA haplotypes. RESULTS: We revealed that G. roeselii includes at least 13 cryptic species or molecular operational taxonomic units (MOTUs), mostly of Miocene origin. A substantial Pleistocene diversification within-MOTUs was observed in several cases. We evidenced secondary contacts between very divergent MOTUs and introgression of nDNA. The Miocene ancestors could live in either lacustrine or riverine habitats yet their presumed geographic localisations overlapped with those of the Neogene lakes. Several extant riverine populations had Pleistocene lacustrine ancestors. DISCUSSION: Neogene divergence of lineages resulting in substantial cryptic diversity may be a common phenomenon in extant freshwater benthic crustaceans occupying areas that were not glaciated during the Pleistocene. Evolution of G. roeselii could be associated with gradual deterioration of the paleolakes. The within-MOTU diversification might be driven by fragmentation of river systems during the Pleistocene. Extant ancient lakes could serve as local microrefugia during that time.